Prioritizing Desiredness in Pregnancy of Unknown Location: An Algorithm for Patient-Centered Care. Issue 5 (November 2020) - Flynn, Anne N.; Schreiber, Courtney A.; Roe, Andrea; Shorter, Jade M.; Frarey, Alhambra; Barnhart, Kurt; Sonalkar, Sarita
Abstract : Patient-centered care is one of the six aims for improvement in health care quality outlined by the National Academy of Medicine (previously known as the Institute of Medicine). We propose an algorithm for patients who are presenting with a pregnancy of unknown location that emphasizes pregnancy desiredness to improve patient-centered care. Health care professionals should assess pregnancy desiredness at a patient's initial consultation for evaluation of pregnancy of unknown location; desiredness, along with other clinical criteria, should guide management. For women with an undesired pregnancy, health care professionals should offer expedient active management. Uterine aspiration will allow for quick clinical diagnosis and resolution of the pregnancy. Alternatively, for women with a desired pregnancy or for those who are ambivalent, we recommend careful conservative management. Adopting this algorithm will recenter the patient in the complex management of pregnancy of unknown location. Abstract : Assessing pregnancy desiredness allows for patient-centered care in the management of pregnancy of unknown location.